In-situ leaching uranium mining drilling mud treatment and recycling method and well cementation cement

By treating drilling mud during the uranium leaching process and adding crushed gravel, combining silicate cement and pressurized filtrate, the problem of insufficient cement strength and flowability is solved, the treatment cost and purification pressure are reduced, and the cementing quality is improved.

CN119553976APending Publication Date: 2025-03-04BEIJING RESEARCH INSTITUTE OF CHEMICAL ENGINEERING AND METALLURGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411454395.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

During the uranium leaching process, the water-cement ratio of cement cement usually exceeds 1, resulting in a decrease in cement strength, a risk of slippage during construction, and the cost of mud treatment is high, and the wastewater purification pressure is high after treatment.

Method used

By filtering and crushing the drilling mud, adjusting the fine mud density and adding crushed gravel, combining silicate cement and pressurized filtrate to prepare cemented cement slurry with improved flow and strength.

Benefits of technology

The amount of silicate cement is reduced, the cost of mud treatment is reduced, the cementing strength is improved, and the shrinkage rate after solidification is reduced, thereby reducing the operation volume of secondary slurry replenishment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090049300000111
    Figure BDA0005090049300000111
  • Figure BDA0005090049300000121
    Figure BDA0005090049300000121
Patent Text Reader

Abstract

The invention provides an in-situ leaching uranium mining drilling mud treatment and recycling method and well cementation cement, and particularly relates to the technical field of in-situ leaching uranium mining. The method comprises the steps that drilling mud is filtered, and gravel particles and fine mud are obtained; the density of the fine slurry is adjusted to 1.10-1.20 g / cm < 3 >, and prepared slurry is obtained; the gravel particles are crushed until the particle size is smaller than or equal to 1 mm, and crushed gravel is obtained; adding the crushed gravels into the prepared slurry to obtain mixed slurry; and mixing the mixed slurry with Portland cement and the first slurry press filtrate to obtain the well cementation cement slurry. According to the invention, the well cementation slurry is prepared by combining the slurry generated in the in-situ leaching uranium mining drilling process and the liquid generated by the slurry filter pressing treatment with the ordinary Portland cement, so that not only is the use amount of the well cementation cement reduced, but also part of the slurry and the slurry filter pressing liquid are treated, and the crushed gravels used in the slurry blending link are treated; the cementing strength of well cementation can be effectively improved, and the shrinkage rate after solidification is also reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of in-situ leaching uranium, and in particular to a method for treating and reusing drilling mud for in-situ leaching uranium and cementing cement. Background Art

[0002] At present, cement slurry for in-situ uranium leaching cementing is usually configured with a water-cement ratio of 1:1. During construction, a grouting pipe is used to reversely grout the ore layer. After solidification, it will shrink by 10%-15%, and then a second grouting is performed to make up for the shrinkage. Since the grouting pipe is relatively thin (outer diameter 40mm, inner diameter about 28mm), it is necessary to ensure the feasibility of construction and prevent blockage in the pipe. In actual operation, the water-cement ratio is usually greater than 1, resulting in a decrease in cementing strength. There is a certain risk of slippage when implementing processes such as pressurized injection and piston hole washing in the later stage. After slippage, the leaching liquid and the leaching liquid will cross the layers, and efficient leaching and precise mining cannot be guaranteed. Summary of the invention

[0003] The purpose of the present invention is to provide a method for treating and reusing drilling mud for in situ leaching of uranium and cementing cement to improve the above problems. In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0004] In a first aspect, the present application provides a method for processing and reusing drilling mud for in situ leaching of uranium, comprising:

[0005] Filter the drilling mud to obtain gravel particles and fine mud;

[0006] The density of the fine mud is adjusted to 1.10-1.20 g / cm 3 , to obtain a prepared mud;

[0007] crushing the gravel particles to a particle size less than or equal to 1 mm to obtain crushed gravel;

[0008] adding the crushed gravel into the prepared mud to obtain a mixed slurry;

[0009] The mixed slurry is mixed with silicate cement and the first mud filter press to obtain cementing slurry.

[0010] Optionally, the density of the fine mud is adjusted to 1.10-1.20 g / cm 3 , including: measuring the density of fine mud;

[0011] The second mud filtrate is added according to the density of the fine mud to adjust the density of the fine mud.

[0012] Optionally, the crushed gravel is added to the prepared mud to obtain a mixed slurry, comprising:

[0013] Measure the density of the prepared mud;

[0014] Subtract one-half of the density of the modulated mud from 0.65 to get the ratio of crushed gravel to be added.

[0015] Optionally, the mixing ratio of the mixed slurry, silicate cement and the first mud filtrate is 1:(1.5-2):1.

[0016] Optionally, the first mud filtrate contains a polycarboxylic acid-based water reducer and an early strength agent.

[0017] Optionally, the polycarboxylic acid-based water reducer includes at least one of allyl alcohol polyoxyethylene ether, polyester phenol, polyurethane phenol and polymethacrylate phenol.

[0018] Optionally, the early strength agent includes at least one of sodium chloride, calcium chloride, triethanolamine and triisopropanolamine.

[0019] Optionally, after the mixed slurry is mixed with silicate cement and the first mud filtrate, 0.3-1wt% of an air entraining agent is added, and the mixture is stirred and mixed evenly to obtain cementing slurry.

[0020] Optionally, the pH of the first slurry filtrate and the second slurry filtrate is 6-8, wherein the maximum particle size is ≤1 mm, and the solid phase particle content is ≤0.5 wt%.

[0021] In a second aspect, the present application also provides a cementing slurry, wherein the cementing slurry is produced by the above-mentioned method for treating and reusing in situ leaching uranium drilling mud.

[0022] The beneficial effects of the present invention are:

[0023] The present invention utilizes the mud and mud filter press liquid generated in the process of in-situ leaching uranium drilling after treatment, and combines it with ordinary Portland cement to prepare cementing slurry. This process not only reduces the amount of Portland cement used (depending on the amount added, 8-14% can be saved), but also treats part of the mud and mud filter press liquid, effectively reducing the cost of mud treatment, and also reducing the pressure and energy consumption of the subsequent purification treatment of the mud filter press liquid. By adding treated gravel and mud to Portland cement, the cementing strength can be effectively improved while ensuring fluidity, and the shrinkage rate of cement after solidification can be reduced, thereby reducing the workload of secondary grouting.

[0024] Other features and advantages of the present invention will be set forth in the following description, and in part will become apparent from the description, or may be understood by practicing embodiments of the present invention. DETAILED DESCRIPTION

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0026] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0027] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0028] In-situ leaching of uranium is the main mining process for natural uranium in my country. The uranium-containing leaching solution is lifted from the borehole to the ground through numerous extraction boreholes and then subjected to a series of treatment processes. The treated tailings are then added with a leaching agent and injected into the ore layer through the injection borehole to form a complete cycle. Drilling (nearly 100 holes are drilled in each mining area) is the first step in the development process. The quality of cementing and mud treatment are particularly important during the drilling process. The return mud during the drilling process needs to be centrally recovered, filtered, dehydrated and harmlessly treated. This step is relatively expensive (for example, in a certain mine, the cost of treating the return mud is more than 10,000 yuan for every 400m of drilling). The wastewater generated after the mud is filtered contains a large amount of drilling fluid components and cannot be used directly. It needs to be filtered more finely.

[0029] At present, there are roughly two types of cementing cement in the field of in-situ leaching uranium: Portland cement and slag cement (MTC). Portland cement is the most common, with a higher strength grade and a fast hardening speed, and is suitable for projects with high construction period requirements. The strength grade of slag Portland cement is relatively low, but its later strength increases rapidly, and it has good impermeability, which is suitable for projects with high durability requirements. At the same time, slag Portland cement has a smaller specific gravity, lower hydration heat, better corrosion resistance and heat resistance, but greater water exudation, poor frost resistance, lower early strength, and higher later strength gain rate, so it requires a longer maintenance period.

[0030] For in-situ uranium cementing, it is necessary to ensure good fluidity during grouting and not be easily blocked, and to ensure high strength and low shrinkage after solidification. The above two commonly used cementing cements are difficult to achieve the required effect.

[0031] The present application provides a method for treating and reusing drilling mud for in situ leaching of uranium, comprising:

[0032] Filter the drilling mud to obtain gravel particles and fine mud;

[0033] The density of the fine mud is adjusted to 1.10-1.20 g / cm 3 , to obtain a prepared mud;

[0034] crushing the gravel particles to a particle size less than or equal to 1 mm to obtain crushed gravel;

[0035] adding the crushed gravel into the prepared mud to obtain a mixed slurry;

[0036] The mixed slurry is mixed with silicate cement and the first mud filter press to obtain cementing slurry.

[0037] The drilling mud is filtered, and the filtering process is completed by using a double-layer vibrating screen to screen out gravel particles with a particle size of more than 1 mm.

[0038] As an optional embodiment, the density of the fine mud is adjusted to 1.10-1.20 g / cm 3 , including: measuring the density of fine mud;

[0039] The second mud filter press is added according to the density of the fine mud to adjust the density of the fine mud. The first mud filter press and the second mud filter press are both filter presses obtained by filtering and dehydrating the drilling mud, and are used in two parts. The first mud filter press is preferably added with additives, and the second mud filter press does not need to be added with additives.

[0040] The pH of the first mud filtrate and the second mud filtrate is 6-8, wherein the maximum particle size is ≤1mm, and the solid phase particle content is ≤0.5wt%.

[0041] As an optional implementation, the crushed gravel is added to the prepared mud to obtain a mixed slurry, and the mass fraction of the crushed gravel added is 5%-10% of the prepared mud. The specific steps include:

[0042] Measuring the density of the prepared mud 泥浆密度 ;

[0043] Subtract one-half of the density of the modulated mud from 0.65 to get the addition ratio of crushed gravel P. 添加比例 ; That is, P 添加比例 =-0.5ρ 泥浆密度 +0.65, 1.2 ≥ ρ 泥浆密度 ≥1.1.

[0044] As an optional implementation, the mixing ratio of the mixed slurry, silicate cement and the first slurry filtrate is 1: (1.5-2): 1. Preferably, the silicate cement is PO42.5 silicate cement.

[0045] As an optional embodiment, the first slurry filtrate contains a polycarboxylic acid water reducer and an early strength agent. The polycarboxylic acid water reducer and the early strength agent are added in an amount of 0.5wt%-1.5wt% of the first slurry filtrate.

[0046] As an optional embodiment, the polycarboxylic acid water reducer includes at least one of allyl alcohol polyoxyethylene ether, polyester phenol, polyurethane phenol and polymethacrylate phenol. Adding the polycarboxylic acid water reducer can reduce the shrinkage rate after cementing.

[0047] As an optional embodiment, the early strength agent includes at least one of sodium chloride, calcium chloride, triethanolamine and triisopropanolamine. The early strength agent is preferably a fluorine-free early strength agent, because the introduction of fluoride into the well will cause the ore layer to be easily blocked, which is not conducive to in-situ leaching. In addition to improving the quality of early cementing, the early strength agent also has the effect of increasing the fluidity of the slurry.

[0048] The early strength agent and water reducing agent can be FK-Z and FK-A (Chongqing Fukang Concrete Admixture Co., Ltd.).

[0049] First, determine the approximate ratio of cement to mixed slurry to ensure that the cementing strength meets the requirements. Under this condition, the fluidity can be adjusted by changing the dosage of water reducer and early strength agent.

[0050] As an optional implementation, after the mixed slurry is mixed with silicate cement and the first mud filter press, 0.3-1wt% of air entraining agent is added, and stirring is continued for 2min-3min to mix evenly to obtain cementing cement slurry. The addition of air entraining agent can effectively remove bubbles generated during the solidification process of cementing cement slurry, thereby improving the strength of cement. The air entraining agent can be AEA-1 or HR-AE type air entraining agent.

[0051] The mixed slurry is mixed with silicate cement and the first mud filter press in a cylindrical mixing barrel and stirred. To ensure fluidity, silicate cement can be added at a lower ratio, greater than or equal to 1.5 times of the first mud filter press, and silicate cement can be added a second time depending on the fluidity. The single stirring time is ≥120s, and the mixture is stirred again after a 30S pause (to facilitate bubble precipitation). The stirring and intermittent cycles are repeated 2-4 times until there are no solid balls and no bubbles generated, which is considered qualified. In this process, the solids adhering to the inner wall of the mixing barrel need to be scraped off in time for stirring to ensure a qualified solid-liquid ratio.

[0052] Based on the same inventive concept, the present application also provides a cementing slurry, which is prepared by the above-mentioned in-situ leaching uranium drilling mud treatment and reuse method. The cementing slurry prepared in the present application has a fluidity of ≥300mm, a shrinkage rate after solidification of ≤8.5%, and a cement strength of ≥6.50MPa, which is significantly improved compared with the traditional in-situ leaching uranium cementing slurry.

[0053] The following describes the embodiments of the present invention through specific examples.

[0054] Example 1

[0055] A method for treating and reusing drilling mud from in situ leaching of uranium. Taking the drilling return mud from a mine as an example, the initial density of the return mud is 1.33g / cm 3 A portion of the return mud is sent to the mud treatment station for filter pressing and dehydration treatment. The obtained mud filtrate has a density of 1.05g / cm 3 , standby; density is 3.2g / cm 3 Standard PO42.5 silicate cement is used as standby; the operation steps are as follows:

[0056] S1. The return mud is coarsely screened through a vibrating screen to screen out gravel particles with a particle size greater than 1 mm to obtain fine mud. The density of the fine mud is measured to be 1.24 g / cm 3 ;

[0057] S2. Add the second mud filter press to adjust the fine mud density to 1.15g / cm 3 , to obtain a prepared mud;

[0058] S3, crushing the gravel particles screened out in step S1 to a particle size of less than 1 mm using a rock crusher to obtain crushed gravel; before crushing, particles with larger particle sizes (≥10 mm) can be removed to effectively reduce crushing time and cost;

[0059] S4, according to formula P 碎砾石添加比例 =-0.5ρ 泥浆密度 +0.65Calculate the addition ratio (mass ratio) of crushed gravel, ρ 泥浆密度 The content of crushed gravel is 1.15 g / cm3, so the addition ratio is 7.5%. After adding crushed gravel to the prepared mud, stir evenly to obtain a mixed slurry;

[0060] S5, prepare the first mud filter press liquid, use the mud filter press liquid as a solvent, add 1% by mass of a polycarboxylic acid water reducer and 1% by mass of an early strength agent, in this embodiment, allyl alcohol polyoxyethylene ether water reducer and triisopropanolamine early strength agent, and stir evenly after adding;

[0061] S6, the mixed slurry obtained in step S4, the standard PO42.5 silicate cement, and the first mud filter press prepared in step S5 are stirred and mixed in a stirring barrel at a mass ratio of 1:1.5:1. The total mass of the first mud filter press is 6.43 tons, so 6.43 tons of the mixed slurry treated in step S4 and 9.645 tons of standard PO42.5 silicate cement are added;

[0062] The slurry was fully stirred, with a single stirring time of ≥120s, and stirred again after a 30s pause (to facilitate the precipitation of bubbles), with a stirring paddle speed of 100rpm, and the stirring interval cycle was repeated 3 times until there were no solid balls or bubbles in the stirring barrel;

[0063] The total weight of the slurry obtained was 22.505 tons, and its density was tested to be 1.53 g / cm 3 , the calculated volume is about 14.7m 3 , 90.02 kg of cement air entraining agent was added at a mass ratio of 0.4%, and the mixture was stirred evenly again to obtain cementing cement slurry. The fluidity of the cementing cement slurry obtained by testing was 310 mm, which met the quality requirement of more than 300 mm.

[0064] Example 2

[0065] A method for treating and reusing drilling mud for in-situ leaching of uranium, comprising:

[0066] S1. The return mud is coarsely screened through a vibrating screen to screen out gravel particles with a particle size greater than 1 mm to obtain fine mud. The density of the fine mud is measured to be 1.25 g / cm 3 ;

[0067] S2, add the second mud filter press liquid to adjust the fine mud density to 1.10g / cm 3 , to obtain a prepared mud;

[0068] S3, crushing the gravel particles screened out in step S1 to a particle size of less than 1 mm using a rock crusher to obtain crushed gravel;

[0069] S4, adding crushed gravel in a mass ratio of 10% to the prepared mud; stirring evenly after adding to obtain a mixed slurry;

[0070] S5, preparing the first mud filtrate, using the mud filtrate as a solvent, adding 1.5% of polyurethane phenol water reducer and 1.2% of calcium chloride early strength agent according to the mass ratio, and then stirring evenly to obtain the first mud filtrate;

[0071] S6. Stir the mixed slurry, standard PO42.5 silicate cement, and the first mud filtrate prepared in step S5 in a mixing barrel at a mass ratio of 1:1.7:1; the single stirring time is ≥120s, and the mixture is stirred again after a 30s pause. The stirring paddle speed is 100rpm, and the stirring interval is cycled 3 times until there are no solid balls or bubbles in the mixing barrel; then, cement air entraining agent is added to the slurry at a mass ratio of 0.6%, and the mixture is stirred evenly again to obtain cementing slurry. The fluidity of the cementing slurry obtained by testing is 305mm, which meets the quality requirement of more than 300mm.

[0072] Example 3

[0073] A method for treating and reusing in-situ leaching uranium drilling mud, comprising:

[0074] S1. The return mud is screened through a vibrating screen to remove gravel particles with a particle size greater than 1 mm to obtain fine mud. The density of the fine mud is measured to be 1.22 g / cm 3 ;

[0075] S2, add the second mud filter press liquid to adjust the fine mud density to 1.12g / cm 3 , to obtain a prepared mud;

[0076] S3, crushing the gravel particles screened out in step S1 to a particle size of less than 1 mm using a rock crusher to obtain crushed gravel;

[0077] S4, adding crushed gravel in a mass ratio of 9% to the prepared mud, stirring evenly after adding, to obtain a mixed slurry;

[0078] S5, preparing the first mud filtrate, using the mud filtrate as a solvent, adding 0.7% of polyurethane phenol water reducer and 0.5% of calcium chloride early strength agent according to the mass ratio, and then stirring evenly to obtain the first mud filtrate;

[0079] S6, stirring the mixed slurry, standard PO42.5 silicate cement, and the first mud filtrate prepared in step S5 in a mixing barrel at a mass ratio of 1:2:1; the single stirring time is ≥120s, stirring again after a 30s pause, the stirring paddle speed is 100rpm, and the stirring interval cycle is repeated 3 times until there are no solid balls and no bubbles in the mixing barrel;

[0080] Cement air entraining agent was added at a mass ratio of 1%, and the mixture was stirred evenly again to obtain cementing cement slurry. The fluidity of the cementing cement slurry obtained by testing was 302 mm, which met the quality requirement of more than 300 mm.

[0081] Example 4

[0082] S1. The return mud is coarsely screened through a vibrating screen to screen out gravel particles with a particle size greater than 1 mm to obtain fine mud. The density of the fine mud is measured to be 1.24 g / cm 3 ;

[0083] S2. Add the second mud filter press to adjust the fine mud density to 1.15g / cm 3 , to obtain a prepared mud;

[0084] S3, crushing the gravel particles screened out in step S1 to a particle size of less than 1 mm using a rock crusher to obtain crushed gravel;

[0085] S4, according to formula P 添加比例 =-0.5ρ 泥浆密度 +0.65Calculate the addition ratio (mass ratio) of crushed gravel, ρ 泥浆密度 The content of crushed gravel is 1.15 g / cm3, so the addition ratio is 7.5%. After adding crushed gravel to the prepared mud, stir evenly to obtain a mixed slurry;

[0086] S5, mixing the mixed slurry obtained in step S4, standard PO42.5 silicate cement, and the first mud filtrate (without air entraining agent and water reducing agent) in a mixing barrel in a mass ratio of 1:1.5:1;

[0087] The slurry was fully stirred, with a single stirring time of ≥120s. It was stirred again after an interval of 30s (to facilitate the precipitation of bubbles). The stirring paddle speed was 100rpm, and the stirring interval was cycled 3 times until there were no solid balls and no bubbles in the mixing barrel. The cementing cement slurry was obtained, and the fluidity of the cementing cement slurry was tested to be 300mm, which met the quality requirement of more than 300mm.

[0088] In this application, the truncated cone circular mold method is used to test the fluidity of cement slurry.

[0089] In order to verify the influence of crushed gravel particle size and crushed gravel addition ratio on the performance of cementing slurry, the present application also provides Examples 5-8 and Comparative Examples 1-3.

[0090] Example 5

[0091] The same as Example 1, except that the density of the prepared mud is 1.2 g / cm 3 , the crushed gravel addition ratio is 5%.

[0092] Example 6

[0093] The same as Example 1, except that the density of the prepared mud is 1.1 g / cm 3 , the crushed gravel addition ratio is different to 5%.

[0094] Example 7

[0095] The same as Example 1, except that the density of the prepared mud is 1.1 g / cm 3 , the crushed gravel addition ratio is different to 8%.

[0096] Example 8

[0097] The same as Example 1, except that the density of the prepared mud is 1.1 g / cm 3 , the crushed gravel addition ratio is different from 10%.

[0098] Comparative Example 1

[0099] The same as Example 1, except that the density of the prepared mud is 1.1 g / cm 3 The addition ratio of crushed gravel is 5%, and the particle size of the crushed gravel is 1mm-3mm.

[0100] Comparative Example 2

[0101] The same as Example 1, except that the density of the prepared mud is 1.1 g / cm 3 The addition ratio of crushed gravel is 8%, and the particle size of the crushed gravel is 1mm-3mm.

[0102] Comparative Example 3

[0103] The same as Example 1, except that the density of the prepared mud is 1.1 g / cm 3 The addition ratio of crushed gravel is 10%, and the particle size of the crushed gravel is 1mm-3mm.

[0104] The fluidity test was conducted on the cementing slurries prepared in Examples 5-8 and Comparative Examples 1-3, and a 10 cm*10 cm*10 cm test module was prepared using the prepared cementing slurries. The cement strength of the test module was tested according to GB / T17671-1999. The test results are shown in Table 1.

[0105] Table 1

[0106]

[0107]

[0108] The control group in Table 1 is a cementing cement prepared by the traditional method using a water-cement ratio of 1.2:1, wherein the cement is standard PO42.5 silicate cement.

[0109] It can be seen that when the crushed gravel particle size is larger, the cement strength is higher, but the fluidity decreases significantly. In order to avoid clogging of the grouting pipe, gravel with a smaller particle size needs to be selected; at the same time, after the gravel is added, the fluidity will be slightly reduced, but it will not affect the construction overall, and the strength will be increased by about 11.03-21.2%. In order to balance the fluidity of cementing cement and the strength after curing, and to ensure that both are in the optimal state as much as possible, this application limits the crushed gravel particle size and determines that the density requirement of fine mud is 1.10-1.20g / cm 3 , and proposed a formula for calculating the proportion of crushed gravel added, namely, P 添加比例 =-0.5ρ 泥浆密度 +0.65.

[0110] In order to verify the effects of crushed gravel and additives on shrinkage, the present application also provides Comparative Example 4.

[0111] Comparative Example 4

[0112] This comparative example is substantially the same as Example 1, except that crushed gravel is not added in this comparative example, and the water reducing agent and early strength agent are added at a ratio of 1.5%, and the air entraining agent is added at a ratio of 1%.

[0113] The cement fluidity, cement strength and shrinkage of Example 1, Example 4 and Comparative Example 4 were tested, and the results are shown in Table 2.

[0114] Table 2

[0115] Shrinkage Cement strength (MPa) Fluidity(mm) Example 1 7.7% 7.03 310 Example 4 8.3% 6.92 300 Comparative Example 4 12.1% 6.34 325

[0116] As can be seen from Table 2, the crushed mud, sand, gravel and additives added in this application not only improve the bonding strength of the mixed slurry, but also reduce the shrinkage rate after solidification, which is convenient for construction and reduces the workload of secondary grouting. After the above test comparison, it was unexpectedly found that the effect of crushed gravel on reducing shrinkage is more significant than that of additives (air entraining agent, water reducing agent and early strength agent), and the effect of the two being used in combination is better. Gravel can be used at any time at the construction site. These types of additives have low cost, small dosage and reliable performance.

[0117] Tests show that the strength of the cementing cement prepared by the present invention is increased by 6-9% in effective strength compared with the traditional cementing method, and the shrinkage rate after solidification is reduced to 20-30% of that of the ordinary cementing method.

[0118] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for treating and reusing drilling mud for in situ leaching of uranium, characterized in that: include: Filter the drilling mud to obtain gravel particles and fine mud; The density of the fine mud is adjusted to 1.10-1.20 g / cm 3 , to obtain a prepared mud; crushing the gravel particles to a particle size less than or equal to 1 mm to obtain crushed gravel; adding the crushed gravel into the prepared mud to obtain a mixed slurry; The mixed slurry is mixed with silicate cement and the first mud filter press to obtain cementing slurry.

2. The method for treating and reusing in-situ leaching uranium drilling mud according to claim 1, characterized in that: The density of the fine mud is adjusted to 1.10-1.20 g / cm 3 , including: measuring the density of fine mud; The second mud filtrate is added according to the density of the fine mud to adjust the density of the fine mud.

3. The method for treating and reusing in-situ leaching uranium drilling mud according to claim 1, characterized in that: The method of adding the crushed gravel into the prepared mud to obtain a mixed slurry comprises: Measure the density of the prepared mud; Subtract one-half of the density of the modulated mud from 0.65 to get the ratio of crushed gravel to be added.

4. The method for treating and reusing in-situ leaching uranium drilling mud according to claim 1, characterized in that: The mixing ratio of the mixed slurry, silicate cement and the first mud filtrate is 1:(1.5-2):

1.

5. The method for treating and reusing in-situ leaching uranium drilling mud according to claim 1, characterized in that: The first slurry filtrate contains a polycarboxylic acid-based water reducer and an early strength agent.

6. The method for treating and reusing in-situ leaching uranium drilling mud according to claim 5, characterized in that: The polycarboxylic acid-based water reducer includes at least one of allyl alcohol polyoxyethylene ether, polyester phenol, polyurethane phenol and polymethacrylate phenol.

7. The method for treating and reusing in-situ leaching uranium drilling mud according to claim 5, characterized in that: The early strength agent includes at least one of sodium chloride, calcium chloride, triethanolamine and triisopropanolamine.

8. The method for treating and reusing in-situ leaching uranium drilling mud according to claim 1, characterized in that: After the mixed slurry is mixed with silicate cement and the first mud filtrate, 0.3-1wt% of an air entraining agent is added, and the mixture is stirred and mixed evenly to obtain cementing slurry.

9. The method for treating and reusing in-situ leaching uranium drilling mud according to claim 2, characterized in that: The pH of the first slurry filtrate and the second slurry filtrate is 6-8, wherein the maximum particle size is ≤1mm, and the solid phase particle content is ≤0.5wt%.

10. A cementing slurry, characterized in that: The cementing slurry is prepared by the method for treating and reusing in-situ leaching uranium drilling mud as described in any one of claims 1 to 9.